HUBUNGAN STATUS EKONOMI DAN PENDIDIKAN IBU DENGAN KEKERASAN PADA ANAK (CHILD ABUSE) DI PAUD TARBIYATUS SHIBYAN MOJOKERTO - Peni, Tri; Sudarsih, Sri (JURNAL KEPERAWATAN SEHAT, 2015)
The child abuse often happen in our environment. The parent can do either emotional abuse, verbal abuse, physical abuse or sexsual abuse. The effect of child abuse are to loose traumatic experience from theirselves and continue both other problems physically, psychologically and social. The purpose of this research`is to determine relationship to economic status and educated of mother with child abuse in PAUD Tarbiyatush Shibyan Mojokerto.Method of this study is crossectional analitical, The population amount 82 respondent. Samples used by probability sampling tehnique with simple random sampling tipe. The sample amounts 51 respondent. The independent variable is economic status and mother educated. The dependent variable is child abuse.The results show that more than 50% child abuse are 28 respondent (54,9%), the most mother low educated amount 45,1% mothers and more than 50 % economic status have low respondent (56,9%).The result of chi square test, show that mother educated with child abuse p:0,10, econoic status with child abuse p: 0,001 are related to significant value 0,05. The results of chi-square from independent and dependent variable show that value p<0,05 means the relationship to mother educated and economic status with child abuse.Mother do physically, verbally,and emotionally due to some reasons based on awareness or unawareness. The conclusions of this study show that mothers educated and economic status relate to child abuse. All of parties involved are expected to teach parents how to take care child the best and add fairly some one abuse for unrepeat action againKeywords: Child abuse, economic status, education mother